The Cost of Complying with Human Rights Treaties : The Convention on the Rights of the Child and Basic Immunization - Gauri, Varun (2012)
The determinants of compliance with human rights treaties likely vary according to the right in question, yet heterogeneity in the pathways through which ratification affects various human rights outcomes has received limited attention. This paper first develops an account of treaty compliance that incorporates the intrinsic benefits to the state of compliance, regime costs associated with certain rights, the political costs that NGOs, judges, and others are able to impose for non-compliance, and the fiscal and economic costs of compliance. The paper argues that for child survival rights, fiscal and economic costs are likely to be dispositive, and that as a result richer countries are more likely to comply. The paper then uses an instrumental variable approach to investigate whether ratification of the Convention of the Rights of the Child was associated with stronger effort at the country level on child survival rights. It finds that ratification of the CRC was correlated with a subsequent increase in immunization rates, but only in upper middle and high income countries.